Técnicas adotadas e utilização de sementes de soja em Rondonópolis, Mato Grosso - Calaça, Antonio João Moreira (2011)
The application of good quality seeds is fundamental to farming success. Estimation of seed utilization in Rondonópolis, the state of Mato Grosso, Brazil, provided by ABRASEM in the last 10 years, shows seed utilization rate ranging 85 to 95%, with setting around 90% in the last 3 crop seasons. Farmers make high utilization of modern technology, thus demanding high yield seeds. The objective of this study is to estimate the utilization rate of soybean seeds, and to verify utilization conditions of available technologies for improving seeds yield. To estimate these values a drill box survey method was used. A total of 100 samples were collected over soybean producing regions of Rondonópolis, in the state of Mato Grosso, Brazil, during the 2010/2011 crop planting season. Farming fields were visited at random at planting time, where planter operators were approached and a sample of 1 kg was taken from the drill box. In addition to collecting seed sample, which was also used to assess mechanical damage, other information was obtained, in particular the source of the seed used. After evaluation of seed quality and data analysis, a commercial soybean seed utilization rate in Rondonópolis, in the state of Mato Grosso, Brazil, was found to be above 88%; estimates of over 54% of soybean farm fields are planted with seeds which mechanical damage index is above ideal level; in Rondonópolis, state of Mato Grosso soybean farmers make use of top technology; over 100% of varieties are protected.